2018
DOI: 10.1021/acs.est.8b00791
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Water Lead Levels During the Flint Water Crisis

Abstract: In April 2014, the drinking water source in Flint, Michigan was switched from Lake Huron water with phosphate inhibitors to Flint River water without corrosion inhibitors. The absence of corrosion control and use of a more corrosive source increased lead leaching from plumbing. Our city-wide citizen science water lead results contradicted official claims that there was no problem- our 90th percentile was 26.8 μg/L, which was almost double the Lead and Copper Rule action level of 15 μg/L. Back calculations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 142 publications
(150 citation statements)
references
References 31 publications
4
145
0
1
Order By: Relevance
“…This is despite the fact that there were biases in the data, as the sites sampled were not representative of Flint housing stock (Goovaerts ). Even the 90th percentile values for the residential testing and that reported by Pieper et al (), which include data from non‐Tier 1 sites, are reasonably consistent with those testing programs where the sites are believed to be all Tier 1. There is a decline in the 90th percentile values over time and after fall 2016, the 90th percentile WLLs were consistently below the AL of 15 μg/L.…”
Section: Other Datasupporting
confidence: 81%
See 4 more Smart Citations
“…This is despite the fact that there were biases in the data, as the sites sampled were not representative of Flint housing stock (Goovaerts ). Even the 90th percentile values for the residential testing and that reported by Pieper et al (), which include data from non‐Tier 1 sites, are reasonably consistent with those testing programs where the sites are believed to be all Tier 1. There is a decline in the 90th percentile values over time and after fall 2016, the 90th percentile WLLs were consistently below the AL of 15 μg/L.…”
Section: Other Datasupporting
confidence: 81%
“…The data presented by Pieper et al () are shown in Figure . The 90 percentile levels for the independent testing ( n = 144) are also shown in Figure .…”
Section: Other Datamentioning
confidence: 99%
See 3 more Smart Citations